(untitled) - United States Department of Agriculture; Natural Resources Conservation Service (Lincoln, 1996)
The purpose of this manual is to document methodlogy and to serve as a reference for the laboratory analysyst.
Keywords: Soil surveys,Thổ nhưỡng